Application Method of Value Stream Mapping to Increase Competitiveness in a Textile and Apparel Company - Ortiz Porras, Jorge (2023)
The textile and apparel sector is one of the most relevant and representative in Peru, due to its tradition and its contribution to the national economy. In recent years, however, it has had to become more competitive, largely due to the entry of international textile product suppliers into the local market. Therefore, companies that comprise this sector must adopt tools that will allow them to increase their productivity. In view of this situation, this research aimed to develop and implement an application model using Value Stream Mapping (VSM) in a textile and apparel company that manufactures garments for export, demonstrating at the same time that VSM is the best tool to visualize the entire supply chain in a single document. It also makes it possible to identify areas of opportunity, perceive the contribution of direct value to the products, distinguish forms of waste, and identify bottlenecks. The methodology adopted for the research is a case study, due to the use of various sources of information, including personal and documentary sources, and the conditions for its development. The results show the determination of the optimal takt time (1060.08 s), and the reduction in the lead time from 20.87 days in the current state map to 16.7 days in the future state map, thus contributing to the improvement of the company’s competitiveness.